Soil Inoculation With Beneficial Microbes Buffers Negative Drought Effects on Biomass, Nutrients, and Water Relations of Common Myrtle - Azizi, Soghra; Tabari, Masoud; Abad, Ali Reza Fallah Nosrat; Ammer, Christian; Guidi, Lucia; Bader, Martin K.-F. (Frontiers in Plant Science, 2022)
Common myrtle (Myrtus communis L.) occurs in (semi-)arid areas of the Palearctic region where climate change, over-exploitation and habitat destruction imperil its existence. The evergreen shrub is of great economic and ecological importance due to its pharmaceutical value, ornamental use, and its role in urban greening and habitat restoration initiatives. Under greenhouse conditions, we investigated the effect of soil inoculation with arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR) on biomass allocation, water relations and nutritional status of drought-stressed myrtle seedlings. Single and dual AMF (Funneliformis mosseae, Rhizophagus irregularis) and PGPR (Pseudomonas fluorescens, P. putida) soil inoculations were applied to myrtle seedlings growing under different soil water regimes (100%, 60%, and 30% of field capacity) for six months using a full factorial, completely randomized design. AMF and PGPR treatments, especially dual inoculations, alleviated negative drought effects on biomass and morpho-physiological traits, except for water-use efficiency, which peaked under severe drought conditions. Under the greatest soil water deficit, dual inoculations promoted leaf biomass (104-108%), root biomass (56-73%), mesophyll conductance (58%) and relative water content (1.4-fold) compared to non-inoculated controls. Particularly dual AMF and PGPR inoculations stimulated nutrient dynamics in roots (N: 138-151%, P: 176-181%, K: 112-114%, Ca: 124-136%, Mg: 130-140%) and leaves (N: 101-107%, P: 143-149%, K: 83-84%, Ca: 98-107%, Mg: 102-106%). Our findings highlight soil inoculations with beneficial microbes as a cost-effective way to produce highly drought resistant seedling stock which is vital for restoring natural myrtle habitats and for future-proofing myrtle crop systems.